Application of exifine in etiotropic treatment of zooanthroponotic trichophytia - Z. R. Hismatullina; R. U. Danilenko; A. U. Sultanbaeva; O. R. Mukhamadeeva (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
We have studied effect of Exifine on the dynamics of infectious process and some parts of the immune response at different stages of zooanthroponotic trichophytosis development. Functional activity of neutrophils, CD3, CD4, CD8, CD16, CD72, HLA-DR lymphocyte markers, TNFa, IL-1 β, IL-4 and IFN-γ cytokines were determined using immunological studies. Histomorphological changes of affected hair were studied during treatment. Effectiveness of Exifine at zooanthroponotic trichophytosis of scalp and smooth skin in children has been proven: mycological cure and persistent therapeutic effect. Exifine has no immunosuppressive activity as observed in Griseofulvin treatment.